Association of exposure to hydrocarbon air pollution with the incidence of atopic dermatitis in children - Chieh Wang; Chang-Ching Wei; Lei Wan; Cheng-Li Lin; Jeng-Dau Tsai (Italian Journal of Pediatrics, 2021)
Abstract Background There is growing evidence suggesting that air pollution may act as an important environmental risk factor in the development and aggravation of childhood atopic dermatitis (AD). Methods We collected data from the Taiwan National Health Insurance (NHI) research database and linked the data to the Taiwan Air Quality-Monitoring Database. From January 1, 2000 to December 31, 2012; children aged below 18 years were selected from the database and followed longitudinally until the diagnosis of AD, withdrawal from the NHI, or December 31, 2012. Children with missing data or those diagnosed with AD before enrolment in this study were excluded. We measured the incidence rate and hazard ratios (HRs) for AD and stratified them by quartiles (Q1–Q4) of air pollutant concentration. Multivariable Cox proportional hazards models were also applied by adjusting for age, sex, monthly income, and level of urbanization. Results When compared with the concentrations of pollutants in the Q1 quartile, the adjusted HR for AD increased with an increase in the exposure concentrations of total hydrocarbons (THCs), non-methane hydrocarbons (NMHCs), and methane (CH4) from 1.65 (95% confidence interval [CI]: 1.47–1.84) to 10.6 (95% CI: 5.85–7.07), from 1.14 (95% CI: 1.06–1.24) to 2.47 (95% CI: 2.29–2.66), and from 1.70 (95% CI: 1.52–1.89) to 11.9 (95% CI: 10.8–13.1), respectively. Patients exposed to higher levels of THCs, NMHCs, and CH4 exhibited greater incidence rates of childhood AD. Conclusions The present study demonstrated that exposure to higher concentrations of THCs, NMHCs, and CH4 were associated with an increased risk of childhood AD.